Purification, Preliminary Structural Characterization, and In Vitro Inhibitory Effect on Digestive Enzymes by β-Glucan from Qingke (Tibetan Hulless Barley) - Jialiang Hu; Yue Wu; Huifang Xie; Wanyin Shi; Zhiyuan Chen; Dan Jiang; Hui Hu; Xiangwei Zheng; Jian Xu; Yuejun Yang; Yuancai Liu (Advances in Polymer Technology)
Background and Objective. Qingke (Tibetan hulless barley, Hordeum vulgare L.) contains a high content of β-glucan among all the cereal varieties. Although β-glucan has multiple physiological functions, the physiological function of qingke β-glucan was few studied. In this study, the β-glucan was isolated, purified, determined the structural characterization, and measured the inhibitory activity to enzymes correlating blood sugar and lipid. Methods. β-Glucan was isolated from enzymatic aqueous extract of qingke by using deproteinization, decolorization, DEAE-52 column chromatography, and sepharose CL-4B agarose gel column chromatography. The structure of the β-glucan was determined using FT-IR and 13C-NMR spectra analysis, and molecular mass by use of HPSEC-dRI-LS. The kinematic viscosity was measured. The inhibitory effects of this β-glucan on four enzymes were investigated. Results. This β-glucan had a uniform molecular weight of 201,000 Da with β-(1⟶4) as the main chain and β-(1⟶3) as a side chain. The β-glucan presented a relatively strong inhibitory activity on α-glucosidase, moderate inhibition on invertase, and a weak inhibition on α-amylase, whereas it did not inhibit lipase. Conclusion. The study indicates that the enzymatic β-glucan from qingke has the potential as natural auxiliary hypoglycemic additives in functional medicine or foods.